Analysis of the National Education Councils during the single-party era in Turkey - Göktürk, Duygun. (Thesis (M.A.)-Bogazici University. Institute for Graduate Studies in Social Sciences, 2006., 2006)
The present study analyzes the National Education Councils (Milli Eğitim Şuraları) and the decisions of the meetings during the single-party era in relation to the development of education policies in Turkey. The particular focus of analysis is the development of the Turkish education system after the establishment of the Republic of Turkey. Single-party era years were chosen in order to analyze the construction and development of the Turkish education system within the years of nation-building process. In embarking on building a new nation-state, education was conceived as the most important foundation. As it developed under the Republic, the National Educational Council, as one of the policy-making bodies of the National Ministry of Education, was established aimed to develop and construct the Turkish education system. Therefore the three National Education Councils and the reports are important in terms of understanding the forces and factors behind the formulation and implementation of all educational policies during the single-party era. In the light of the analysis, thegeneral evaluation of the Councils can be made according to the modernization process and its sanctions in the nation-building process; the citizen model that theRepublic wanted to create via education, and the political forces behind theformulation of education system and their meaning in the social context. All three National Education Councils and their decisions were concentrated around these determinatives.
Keywords: Education -- Research -- Turkey.; Education -- Turkey.